Desenvolvimento de equipamento para municiamento automático de carregadores para pistola - Macedo, Cristiano Vargas (2017)
Carrying out the automatic loading of magazines is essential, since all pistols produced have their magazines loaded to pass a shooting test, where it is necessary to develop a modular design, the national manufacturing and low cost of a loader equipment that allow a shorter time and greater ease in loading magazines, eliminating manual loading. In this context, a project methodology was used to elaborate the design of the equipment, which is composed of four phases: project specification, conceptual design, preliminary design and detailed design, used sequentially, having great importance in the organization and elaboration of the project and functional design of the equipment. We sought to develop a flexible and robust national manufacturing equipment capable of loading different calibres of ammunition, being .380 ACP, 9mm luger, .40 S & W and .45 ACP, with the possibility of performing the quantity of ammunition per loader, whether single stack or double stack, has a relatively small number of components, and allows the use of its concept in the different arms industries that produce pistols, shooting ranges clubs for practice with a reduction of up to 60% in the loading magazine time, guaranteeing the elimination of ergonomic risks